2019
DOI: 10.1016/j.redox.2018.101080
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter induces inflammatory cytokine production via activation of NFκB by TLR5-NOX4-ROS signaling in human skin keratinocyte and mouse skin

Abstract: Particulate matter (PM) increases levels of pro-inflammatory cytokines, but its effects on the skin remain largely unknown. We investigated the signal transduction pathway and epigenetic regulatory mechanisms underlying cellular inflammation induced by PM with a diameter of ≤ 2.5 (PM2.5) in vitro and in vivo. PM2.5-treated skin keratinocytes produced various inflammatory cytokines, including IL-6. The binding of PM2.5 to TLR5 initiated intracellular signaling through MyD88, and led to the translocation of NFκB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 34 publications
5
82
0
Order By: Relevance
“…Similar to what is known with UV exposure, pollution (particulate matter) has been reported to trigger inflammation in keratinocytes [36,37]. While an inflammatory response can resolve poststress, it has been suggested that this resolution becomes less efficient with aging and leads to a persistent sub-chronic inflammatory state.…”
Section: Discussionmentioning
confidence: 83%
“…Similar to what is known with UV exposure, pollution (particulate matter) has been reported to trigger inflammation in keratinocytes [36,37]. While an inflammatory response can resolve poststress, it has been suggested that this resolution becomes less efficient with aging and leads to a persistent sub-chronic inflammatory state.…”
Section: Discussionmentioning
confidence: 83%
“…Exposure to PM causes epithelium damage, and endothelial dysfunction has been reported previously [8,9,38]. PM induce skin damages or diseases mainly through stimulating inflammatory response and oxidative stress [5,39]. Ryu et al investigated that PM induced epidermic inflammatory response in human keratinocytes [39].…”
Section: Discussionmentioning
confidence: 96%
“…PM induce skin damages or diseases mainly through stimulating inflammatory response and oxidative stress [5,39]. Ryu et al investigated that PM induced epidermic inflammatory response in human keratinocytes [39]. The results indicated that PM significantly stimulated the expression of pro-inflammatory cytokines through activating NF-κB pathway [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the body is infected or repairs wounds, it permanently activates and chemotactically accumulates a large number of white blood cells (such as macrophages, neutrophils, lymphocytes, and dendritic cells) at the site of injury by releasing cytokines/chemokines (such as interleukin-6/10 (IL-6/10) [38,39] and tumor necrosis factor-α (TNF-α)) [40], growth factors (transforming growth factor-β (TGF-β)) [41], matrix metalloproteinases (MMPs) [42], vascular endothelial growth factor (VEGF) [43], reactive oxygen species (ROS) metabolites, and other substances [44]. These inflammatory cytokines not only recruit inflammatory cells to amplify inflammation at the tumor site [45] but also form a new environment [46], leading to the destruction and atrophy of normal tissues [47] and promoting mass production of the tumor matrix and blood vessels [48].…”
Section: Changes In the Tumor Inflammatory Environmentmentioning
confidence: 99%